Tensile properties of continuous E-glass and basalt fiber reinforced polypropylene composites - Bekem, Aylin; Dogu, Mustafa; Unal, Ahmet (CARL HANSER VERLAG, 2017)
Polypropylene has a higher melt viscosity and low surface tension that lead to harder interfacial bonding in composite production. However, it has some advantages like good impact strength, low water absorption, low density, low coefficient of friction and high insulating properties. In this study, E-glass fiber and basalt fiber were used to reinforce polypropylene. Powder with compatibilizer was impregnated to E-glass and basalt fiber and prepregs were produced. Then, these were embedded into polypropylene matrix and samples were obtained. Tensile properties and fiber volume ratios were determined. Also, T-peel test was applied to check bonding at the fiber-matrix interface. Fractured parts were observed and fracture types were investigated. It was concluded that both had similar bonding strength, but E-glass reinforced polypropylene composite had higher tensile properties than basalt fiber reinforced composite.
Keywords: Basalt fiber; E-glass; polypropylene; tensile properties; MECHANICAL-PROPERTIES; BEHAVIOR; Materials Science